2017
DOI: 10.3390/nu9111216
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency Anemia, Not Iron Deficiency, Is Associated with Reduced Attention in Healthy Young Women

Abstract: Women of reproductive age are at increased risk for iron deficiency (ID) and iron deficiency anemia (IDA), with both implicated in decreased cognitive function (CF). Obesity may complicate this association via inflammatory-mediated ferritin elevation. This cross-sectional study examined the association between hematological iron status (iron replete (IR), ID or IDA) and CF in healthy, young (18–35 years) women of normal-weight (NW: BMI 18.5– 24.9 kg/m2) or obese-weight (OB: BMI >30 kg/m2). Participants complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 45 publications
0
26
0
3
Order By: Relevance
“…Physical inactivity, which is often strongly associated with obesity, has also been linked with cognitive decline or reduced cognitive performance [2024]. Iron status also may impact cognitive function [25, 26]. The impact of these confounding variables should be considered when examining the relationships between n-3 PUFA status and cognitive function, but unfortunately, studies examining these relationships rarely measure or adjust for these.…”
Section: Background/objectivesmentioning
confidence: 99%
“…Physical inactivity, which is often strongly associated with obesity, has also been linked with cognitive decline or reduced cognitive performance [2024]. Iron status also may impact cognitive function [25, 26]. The impact of these confounding variables should be considered when examining the relationships between n-3 PUFA status and cognitive function, but unfortunately, studies examining these relationships rarely measure or adjust for these.…”
Section: Background/objectivesmentioning
confidence: 99%
“…Due to the increased demand for iron, normal diet cannot meet the demand of some pregnant women for iron, especially women with an already established iron deficiency [ 4 ]. Anemia not only can increase the risk of adverse pregnancy outcomes [ 5 7 ], but may reduce cognitive function [ 8 ], and reduce work efficiency [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The health effects of iron deficiency without anemia are still debated[27,28]. In previous blood donor research, ferritin levels did not affect self-reported health[29] or the presence of restless leg syndrome [30].…”
Section: Introductionmentioning
confidence: 99%